A PET-CT study on the specificity of acupoints through acupuncture treatment in migraine patients - Yang Jie; Zeng Fang; Feng Yue; Fang Li; Qin Wei; Liu Xuguang; Song Wenzhong; Xie Hongjun; Chen Ji; Liang Fanrong (BMC, 2012)
Abstract Background In the field of acupuncture research, the topic of acupoint specificity has received increasing attention, but no unified conclusion has been reached on whether or not acupoint specificity exists. Furthermore, the majority of previous acupuncture neuroimaging studies have been performed using healthy subjects. In this study, patients with migraine were used to investigate acupoint specificity. Methods Thirty patients with migraine were enrolled and randomized into three groups: Traditional Acupuncture Group (TAG), Control Acupuncture Group (CAG), and Migraine Group (MG). The TAG was treated by acupuncture stimulation at Waiguan (TE5), Yang Lingquan (GB34), and Fengchi (GB20). The CAG was treated at Touwei (ST8), Pianli (LI6), and Zusanli (ST36). The MG received no treatment. Positron emission tomography with computed tomography (PET-CT) was used to test for differences in brain activation between the TAG and CAG versus MG, respectively. Results Traditional acupuncture treatment was more effective for pain reduction than control acupuncture treatment. The TAG showed higher brain metabolism than the MG in the middle temporal cortex (MTC), orbital frontal cortex (OFC), insula, middle frontal gyrus, angular gyrus, post-cingulate cortex (PCC), the precuneus, and the middle cingulate cortex (MCC). Metabolism decreased in the parahippocampus, hippocampus, fusiform gyrus, postcentral gyrus, and cerebellum in the TAG compared with the MG. In the CAG, metabolism increased compared with the MG in the MTC, supratemporal gyrus, supramarginal gyrus, and MCC, whereas metabolism decreased in the cerebellum. Conclusions Acupuncture stimulation of different points on similar body regions in migraine patients reduced pain and induced different levels of cerebral glucose metabolism in pain-related brain regions. These findings may support the functional specificity of migraine- treatment-related acupoint. Trial registration The number of our clinical trial registration is: ChiCTR-TRC-11001813, and the protocol and inclusion criteria have already been registered as ChiCTR-TRC-11001813.